Implikasi Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 tentang Cipta Kerja Sektor Perkebunan terhadap Eksistensi Masyarakat Hukum Adat - Rohmah Dwi Cahyanigsih; Raka Haikal Anfasya; Akhmad Kautsar Fattah; Abdul Haris Nafis; Handoyo Prasetyo; Atik Winanti (STIKes Ibnu Sina Ajibarang, 2025)
This study analyzes the impact of Government Regulation in Lieu of Law (Perppu) No. 2 Year 2022 on Job Creation, particularly in the plantation sector, on the rights of Masyarakat Hukum Adat (MHA). The initial purpose of this Perppu was to increase investment through simplification of regulations and acceleration of licensing, but the formulation of existing norms and regulations can threaten the existence of MHA. This research is a normative research and uses a legislative approach by analyzing primary and secondary legal materials, and using John Rawls' Theory of Justice and Mochtar Kusumaatmadja's Theory of Development Law. The results show that there are significant changes in the application of Perppu No. 2 Year 2022 on Job Creation compared to Law No. 34 Year 2014 on Plantations, including changes in land area limitations, elimination of environmental permits, and elimination of criminal sanctions related to permits and the environment. The implications of the implementation of this Perppu are that it exacerbates the marginalization of Indigenous Peoples, ignores customary rights, and causes overlapping land tenure, as well as ecosystem and environmental damage. This research suggests several strategic steps: accelerating the inventory of customary land and the granting of customary rights certificates, requiring MHA to be involved in every stage of decision-making through FPIC mechanisms, and passing a special law for MHA. Investment policies should also focus on sustainable development with stricter environmental standards than at present.